Estimation of tanker vessel's performance through key performance indicators using fuzzy logic models - Πολυμενοπούλου, Αικατερίνη- Μαρία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Μελέτης Πλοίου και Θαλάσσιων Μεταφορών, 2016)
Performance is nowadays a meaning that everyone wants to estimate in his everyday life and especially in his carrier. Both for humans but mainly for companies and industries the sense of performance is crucial them for them and many efforts have been made in order to evaluate and improve it. The progress of performance evaluation can be succeeded through the use of well known Key Performance Indicators (KPIs). KPIs can be used for evaluating all types of performance according to each organization’s scope and nature. In the specific diploma thesis we will focus exclusively to safety, health and safety, security and environmental KPIs. With aim to investigate throughout the above fields of KPIs in the subject diploma thesis we will present eight different industries concerning the above fields, safety, health and safety, security and environment. The main reason of this is to find out which KPIs are in used by every industry, which are the common ones and how the examined industries differs or resembles with each other. The examined industries are road, rail, aviation, chemical, nuclear power plan, offshore, ports and shipping. After having completed the KPIs investigation in all the mentioned industries, the subject diploma thesis focuses in the shipping industry and more specific to tanker vessels in order to create a model which will combine at each field a set of KPIs and to produce a total estimation of the performance of one tanker vessel. This progress will be completed through Fuzzy Logic and more specific through Matlab Fuzzy Logic Toolbox. Through this, we will produce four different Fuzzy Models, which will evaluate safety, health and safety, security and environmental performance respectively. The produced models can be used from a shipping company for every tanker vessel separately. The first step in order to create the mentioned models is the selection of the right KPIs. Having them selected you will find next the use of Fuzzy Models in 30 different tanker vessels in order to conclude to an average performance. By this way each tanker’s performance can not only to be evaluated by our created models but also to be compared with the average performance.